Health Education Effected Public Knowledge To Prevention Of Dengue Hemorrhagic Fever (DHF) - Merbawani, Raras; Asef Wildan Munfadlila (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
Problems The government's present approach to the challenges the DHF disease faces in Indonesia is insufficient. Though, in order to regulate the DHF condition, public support is essential. The fact that the general public does not participate in Mosquito Nest Eradication (PSN) initiatives shows how poorly understood and known DHF illness prevention is by the general population. Examine the impact of health education on the community's awareness of DHF prevention. Pretest-posttest design with a single group, pre-experimental investigation. The population of Village Sumberwuluh Subdistrict Dawarblandong Regency Mojokerto, which consists of 289 homes and is entirely under inquiry, was represented by one responder who was between the ages of 18 and 35 in each of the 289 households. This is a simple random sampling technique. 44 people comprise the huge sample. questionnaire-based instrument study using SAP. The results showed that 32 respondents (72.7%) had sufficient knowledge of DHF prevention before obtaining health education, and 23 respondents (52.3%), after getting health education, had sufficient knowledge of DHF prevention. Based on the Wilcoxon Signed Rank statistical test results, H1 is accepted and H0 is denied, which indicates that health education has an impact on community understanding on DHF prevention. When more data is acquired and health education is observed, a better understanding of DHF prevention is attained.